Sacred area surrounded by the Temenos fence - Al-Zaidi, Kazem Abdullah Attia; Al-Ramahi, Mohamed Brij Hattab (Al-Adab Journal, 2020)
Take up this research the holy area, which is the nucleus of the city and its components (the temple and the place). The location of the holy area differed with respect to the city, according to the method of planning the city and according to the historical periods. In the south, the city occupied center of the city. Set aside that it became part of the wall, either in the modern Babylonian, where the ancient Sumerian concepts were combined with the Assyrian style, and they were concentrated in isolation from the royal places. Most of the holy areas were surrounded by a wall called in the Sumerian language (TEMEN) and the Akkadian language (temmennu) and means the basis.